(untitled) (Research, Society and Development, 2021)
The teaching approach using business simulation games can generate a series of benefits in the teaching-learning process of disciplines in the Production Engineering course. Therefore, the objective of the article is to raise the characteristics of the use of games, through a research carried out in articles published in the annals of the National Meeting of Production Engineering (ENEGEP) in the period from 2014 to 2019, with the search terms: company game (s), serial game (s), serious game (s), gamification and gamification. Through the 21 selected publications, a qualitative research was carried out, through the content analysis of the abstracts of the articles, using the IRaMuTeQ software, in order to explore the related terms in the publications. The use of the IRaMuTeq software as a tool for processing qualitative data provided statistical information on the text, as well as the Descending Hierarchical Classification (CHD), similarity analysis and the word cloud. The results show that games and their related terms are closely linked to the teaching-learning process, especially the terms competence, leverage and experience, which are terms that indicate objectives of the application of games.